التلوث النفطي في طحالب ساحل خليج عدن - اليمن (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
The contamination of algae by oil is posing a great threat to public health and marine life, wherever there is oil pollution. Fifteen different species of algae were studied from Gulf of Aden of Yemen. The extract of algae were examined for the content of oil. They were estimated by GC/MS and quantification was achieved by standard hydrocarbons. It was observed that algae extract contained oil. In the algae range of these oil was found to be from ND ng g-1 to 4.5 ng g-1. These algae were found to be contaminated and it is urgently needed to control the source of contamination. يشكل تلوث الطحالب بالنفط خطرا عظيما على الصحة العامة والحياة البحرية. وفي هذا البحث تمت دراسة خمسة عشر نوع مختلفة من الطحالب. لقد تم تعيين تراكيز النفط في هذه الطحالب بواسطة جهاز GC/MS، وعرفت تراكيزها بواسطة محاليل هيدروكربونه قياسية. وفي هذه الدراسة لوحظ احتواء الطحالب على النفط. ففي الطحالب المأخوذة من ساحل خليج عدن اليمني كانت التراكيز في الحدود ما بين صفر و 4.5 نانو جرام/ جرام ولقد أثبتت هذه الدراسة أن الطحالب المدروسة تحتوي على كميات متباينة من النفط وأن هناك حاجة ملحة لمراقبة هذه التراكيز وضبط مصادر هذه الملوثات.